2017
DOI: 10.1080/15459624.2017.1358818
|View full text |Cite
|
Sign up to set email alerts
|

Particle size distribution: A key factor in estimating powder dustiness

Abstract: A wide variety of raw materials, involving more than 20 samples of quartzes, feldspars, nephelines, carbonates, dolomites, sands, zircons, and alumina, were selected and characterised. Dustiness, i.e., a materials' tendency to generate dust on handling, was determined using the continuous drop method. These raw materials were selected to encompass a wide range of particle sizes (1.6-294 µm) and true densities (2650-4680 kg/m). The dustiness of the raw materials, i.e., their tendency to generate dust on handlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Here it seems that near spherical materials with d 50 > 20 µm have higher potential to release respirable particles (e.g., clay OpTiMat, microspheres) when compared to materials with smaller particle diameters (e.g., dolomite, kaolinite, calcined clay, and calcite). Similar observations were previously reported for micron-sized and nanoscale powders [35,37,[70][71][72][73]. This is probably due to the weaker cohesive forces and consequently material dustiness is higher and particles with small diameters are more probable to be released.…”
Section: Materials Characteristics and Propensity To Dust Releasesupporting
confidence: 88%
See 1 more Smart Citation
“…Here it seems that near spherical materials with d 50 > 20 µm have higher potential to release respirable particles (e.g., clay OpTiMat, microspheres) when compared to materials with smaller particle diameters (e.g., dolomite, kaolinite, calcined clay, and calcite). Similar observations were previously reported for micron-sized and nanoscale powders [35,37,[70][71][72][73]. This is probably due to the weaker cohesive forces and consequently material dustiness is higher and particles with small diameters are more probable to be released.…”
Section: Materials Characteristics and Propensity To Dust Releasesupporting
confidence: 88%
“…The characterization data demonstrate a considerable range in BET-SSA values (e.g., dolomite and TiO 2 with 3.2 and 13 m 2 g −1 , respectively), particle grain sizes (0.25 to 30 µm), bulk densities (0.16-1.09 g cm −3 ), and particle shapes (e.g., plate talc, plate clays, rod calcite, and spherical TiO 2 and dolomite). Therefore, establishing a general relationship between emission patterns and materials physicochemical characteristics might be challenging [70][71][72][73].…”
Section: Raw Materials Characterizationmentioning
confidence: 99%
“…According to the literature, significant correlations may be observed between particle SSA and dustiness when comparing different quartzes (López-Lilao et al, 2016) and different kaolin samples (López-Lilao et al, 2015). Previous works (López Lilao et al, 2017) have shown that, for approximately spherical and dry materials, coarser mean diameters present a higher potential for release of fine particles. Thus, dustiness depends on the amount of fine particles and the material's ability to release such fine particles.…”
Section: Comparison Between Dustiness and Exposure Concentrationsmentioning
confidence: 98%
“…Particle mass was calculated by using mobility particle diameter and effective density as in Koivisto et al (2012b). Particle density during packing was assumed to be 2.55 g cm -3 as it is the materials' mean density (López Lilao et al, 2017) described by the provider, and 1.5 g cm -3 during background (Martins et al, 2015). The regional inhalation dose rate, calculated for head airways, tracheobronchial and alveolar regions, was obtained by applying WA particle size concentrations to simplified deposition fraction probability equations for the ICRP human respiratory tract model (ICRP, 2011) as described by Hinds (1999).…”
Section: Particle Inhalation Dosementioning
confidence: 99%